For the Dead: Witnessing Images of Violence in Jonathan Littell's Une Vieille Histoire: Nouvelle Version - Orit Yushinsky Troupin (Studies in 20th & 21st Century Literature, 2020)
This article deals with representing violence and witnessing in Jonathan Littell's novel Une Vieille Histoire: Nouvelle Version. First, I show how by means of renouncing mimetic representation, Littell "weaves" a reality of violence and excessive sensations into a text and creates disturbing abstract-corporeal images that stimulate readers' attention to contemporary prevailing violence in our societies. I then claim that narrators in the novel, in their role as abusers, victims, or witnesses, become fascinated with images of violence that stupefy them, turning them into blinded witnesses who cannot testify on ungraspable and impenetrable images of violence. As witnesses, narrators become gazes, mirrors, and bodies bereft of subjectivity that embody the collapse of witnessing and the violence done to bodies in the text.
Keywords: Littell; Blanchot; corpse-image; violence; witnessing